PENEGAKAN HUKUM PIDANA PEMILU/PILKADA ELEKTRONIK PADA PEMILU/PILKADA SERENTAK 2024 - Pirmansyah, Redi; Junaidi, Junaidi; Merta, Martindo (VARIA HUKUM, 2023)
ABSTRACT Election criminal provisions regulated in Law Number 7 of 2017 concerning General Elections only cover 80 articles of election crimes and do not comprehensively regulate election criminal acts in the electronic field for all applications to be used in the 2024 Election. This can create a legal vacuum or the obscurity of election crimes in the field of electronics in the use of electronic election systems. Although Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions generally regulates electronic crimes, the 11 articles of electronic crimes do not regulate electronic crimes at the time of the election stage. The electronic election crime above will guarantee protection for all applications that will be implemented by the KPU in carrying out the 2024 election stages. In the context of this crime, the "electronic election system" includes all electronic systems used by the KPU in accordance with the Decree of the General Election Commission of the Republic of Indonesia Number 13/TIK.03/14/2022 concerning Plans for Electronic-Based Government Systems. This regulation will provide legal clarity for the prosecution of electronic election crimes in Indonesia Â Â ABSTRAK Ketentuan pidana pemilu yang diatur dalam Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum hanya mencakup 80 pasal tindak pidana pemilu dan tidak secara menyeluruh mengatur tindak pidana pemilu di bidang elektronik untuk semua aplikasi yang akan digunakan dalam Pemilu 2024. Ini dapat menimbulkan kekosongan hukum atau ketidakjelasan pidana pemilu di bidang elektronik dalam penggunaan sistem elektronik pemilu. Meskipun Undang-Undang Nomor 19 Tahun 2016 tentang Perubahan atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik, secara umum mengatur tindak pidana elektronik, namun 11 pasal tindak pidana elektronik tersebut tidak mengatur pidana elektronik pada saat terjadinya tahapan pemilu. Kejahatan pemilu elektronik di atas akan menjamin perlindungan terhadap seluruh aplikasi yang akan diterapkan oleh KPU dalam melaksanakan tahapan pemilu 2024. Dalam konteks tindak pidana tersebut, "sistem elektronik pemilu" mencakup semua sistem elektronik yang digunakan oleh KPU sesuai dengan Keputusan Komisi Pemilihan Umum Republik Indonesia Nomor 13/TIK.03/14/2022 tentang Rencana Sistem Pemerintahan Berbasis Elektronik. Aturan ini akan memberikan kejelasan hukum bagi penindakan kejahatan pemilu elektronik di Indonesia